(untitled) (Global Journal of Computer Science and Technology, 2014)
Visually impaired or blind people faced tremendous challenges daily in accessing the information while on the move or during communicating with the world around them. They had to depend on their sighted colleagues, friends, relatives, or the people on the road to help them with locating places. Our Location Based Information System is such a location based application that works as an audio road guider for the visually impaired people using Open Street Map. Open Street Map (OSM) is a world-wide campaign for developing open source maps. Voice recognition represents a technology that is finally ready for prime time use. In our system we used voice recognition as visually impaired people unable to text searching.